2014
DOI: 10.1111/dsji.12031
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Textbooks: Antecedents of Students’ Adoption and Learning Outcomes

Abstract: Faculty and students are increasingly faced with the opportunity to use electronic versions of textbooks (e-texts). Despite the advantages of e-texts and recent advances in technology, evidence suggests that students are still reluctant to adopt and use e-texts. This situation leads us to investigate two research questions: What factors contribute to students’ acceptance of e-texts? Are there differences between hardcopy texts and e-texts when it comes to course grade? We draw on a variety of perspectives (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 57 publications
0
68
2
1
Order By: Relevance
“…The e-textbooks in these studies are mere replacements of the paper textbooks; thus, none of these studies employ an instructional method that can capitalize on features of the e-textbooks. Consequently, and not surprisingly, they do not report any significant difference in learning due to the media, regardless of whether learning is measured with test scores (Daniel & Woody, 2013;Siebenbruner, 2011), course grades (Shepperd et al, 2008;Terpend et al, 2014), or self-reported learning gains (Giacomini et al, 2013;Ji et al, 2014;Rockinson-Szapkiw et al, 2013).…”
Section: Learning From E-textbooks As Instructional Mediamentioning
confidence: 97%
See 2 more Smart Citations
“…The e-textbooks in these studies are mere replacements of the paper textbooks; thus, none of these studies employ an instructional method that can capitalize on features of the e-textbooks. Consequently, and not surprisingly, they do not report any significant difference in learning due to the media, regardless of whether learning is measured with test scores (Daniel & Woody, 2013;Siebenbruner, 2011), course grades (Shepperd et al, 2008;Terpend et al, 2014), or self-reported learning gains (Giacomini et al, 2013;Ji et al, 2014;Rockinson-Szapkiw et al, 2013).…”
Section: Learning From E-textbooks As Instructional Mediamentioning
confidence: 97%
“…Although there have been a number of studies focusing on the learning effects of etextbooks, most of these studies compare overall impact of e-textbooks to paper textbooks (Daniel & Woody, 2013;Giacomini et al, 2013;Ji, Michaels, & Waterman, 2014;RockinsonSzapkiw, Courduff, Carter, & Bennett, 2013;Shepperd, Grace, & Koch, 2008;Siebenbruner, 2011;Terpend, Gattiker, & Lowe, 2014). The e-textbooks in these studies are mere replacements of the paper textbooks; thus, none of these studies employ an instructional method that can capitalize on features of the e-textbooks.…”
Section: Learning From E-textbooks As Instructional Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…As with textbooks, the key function of e‐textbooks is to facilitate student learning (Terpend et al., ). Some studies have found that e‐textbooks and traditional textbooks yield equivalent learning outcomes (e.g., Weisberg, ), while others have found that e‐textbooks enhance learning for students (e.g., Sun et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A key underlying assumption of previous research is that e‐textbooks are reasonable replacements for traditional textbooks. A review of the literature suggests that this assumption is not necessarily true because prior e‐textbook studies focus on student adoption behavior not how students perceive e‐textbooks fitting their needs (Gattiker, Lowe, & Terpend, ; Lai & Chang, ; Saadé & Bahli, ; Stone & Baker‐Eveleth, ,b; Terpend, Gattiker, & Lowe, ). Indeed, e‐textbooks and textbooks exhibit different features and benefits (Wu & Chen, ).…”
Section: Introductionmentioning
confidence: 99%